Impact of language variables on bilateral trade - Várnagy, Edina (Acta Carolus Robertus, 2022)
The paper attempts to provide a comprehensive picture of different approaches and effects of the language variable in the gravity model, one of the most commonly used tools for the analysing of international trade. The authors from the subject, economics of languages, agree that a common language contributes to the expansion of trade between two countries. In the initial application of the gravitational equation, the language variable was mainly based on the official language of the countries. The reasons are that information about the official languages of countries is easily available. The main focus of these early studies didn’t consider the language effect necessary. Thus, they leave out more complex analyses about languages with unofficial status but significant speakers or the positive effects of language learning. With the development of databases, model specifications, and estimation methods, the common language approach has also changed, and analyses of language proficiency have become more important. This literature review article is aim to acquaint the reader with a field of language economics and to summarize the most important results of the connections between international trade and language and language skills.